Aeromonas Species: An Opportunistic Enteropathogen in Patients with Inflammatory Bowel Diseases? A Single Center Cohort Study. Issue 1 (January 2015) - Lobatón, Triana; Hoffman, Ilse; Vermeire, Severine; Ferrante, Marc; Verhaegen, Jan; Van Assche, Gert
Abstract : Background: The role of Aeromonas species as an enteropathogen in patients with and without inflammatory bowel disease (IBD) is still debated. The aim was to explore the significance of positive Aeromonas stool cultures in IBD and patients without IBD. Methods: Observational retrospective study including all patients with a stool culture positive for Aeromonas between January 2011 and October 2013 at the Leuven University Hospitals. Demographics, clinical, and endoscopic outcomes and laboratory results were analyzed. Results: A total of 77 patients (11 IBD) were identified. In 37 cases, Aeromonas caused a mild self-limited gastrointestinal infection. Among the 40 patients needing antibiotics, 22 presented a mild-to-moderate gastrointestinal infection; 4 suffered from extraintestinal complications; and 4 were coinfected by Campylobacter spp . A. veronii caused more frequently severe infection than the other species (25% versus 5%; P = 0.046). In 2 patients with ulcerative colitis, Aeromonas triggered a moderate-to-severe flare and 2 cases appeared in the context of de novo Crohn's disease. In contrast, in 1 patient with ulcerative colitis and 2 patients with Crohn's disease, Aeromonas caused a mild gastrointestinal infection not worsening the disease activity and in 4 patients with Crohn's disease, it presented in the context of active disease with no clear pathogenic role. Patients with IBD were treated more often with antibiotics (82 versus 41%, P = 0.012) and had more complications (46 versus 14%, P = 0.024). Conclusions: Aeromonas caused mostly mild infections but also moderate and severe infections. A. veronii was more prevalent in patients with IBD and was associated with worse clinical outcomes. Aeromonas caused milder infections in patients without IBD. Other risk factors for severe infection were not found. Abstract : Article first published online 26 November 2014.Supplemental Digital Content is Available in the Text.